THE DEVELOPMENT OF INQUIRY METHOD BASED EXPLANATORY TEXT WITH PISA FRAMEWORK FOR JUNIOR HIGH SCHOOL - Riszky Pabela Pratiwi; Mulyadi Eko Purnomo; Zahra Alwi; Zulkardi Zulkardi (English Review: Journal of English Education, 2023)
Research and development of a module for reading explanatory texts based on inquiry methods and PISA standardized questions has been carried out in class VIII SMP N 52 Palembang. This study aimed to produce reading modules that suit the needs of teachers and students. The research method used was development research with the steps of research on the development of the Jolly and Bolitho and Dick, Carey & Carey models which include identification of needs, exploration of material needs, contextual realization, production of materials, expert validation, one to one evaluation, small group and field tests. Data was collected through questionnaires, interviews, validation sheets, and tests. The results showed that the feasibility aspect of content and presentation obtained a percentage of 84% in the very good category, linguistic feasibility obtained a percentage of 90% and was categorized as very good, graphics obtained a percentage of 76% in the good category, validation questions received a percentage of 85% in the very good category. Practicality in the one-to-one evaluation stage and the small group gets a percentage of 80% in the practical category. The effectiveness measured in the field test is 0.49 and is in the medium category. Thus, the product in the form of a module for reading explanatory texts based on inquiry methods and PISA standardized questions can be used in learning explanatory texts.